Correlation between thermo‐mechanical properties and chemical composition of aged thermoplastic and thermosetting fiber reinforced plastic materials: Korrelation zwischen thermomechanischen Eigenschaften und chemischer Zusammensetzung von gealterten thermo‐ und duroplastischen faserverstärkten Kunststoffen. Issue 5 (May 2017) - Messana, A.; Airale, A. G.; Ferraris, A.; Sisca, L.; Carello, M.
Abstract: In this paper the influence of hygrothermal ageing on the chemical composition, as well as the mechanical and thermal properties of four different composite materials was investigated: woven carbon fibre and glass fibre, with traditional epoxy resin and advanced thermoplastic polyphenylene sulphide (PPS). In particular, hygrothermal tests of 500, 750 and 1000 hours are performed with standard cycling used by most of original equipment manufacturer and car manufacturers. The ultimate strength and Young′s modulus have been verified using tensile and compression tests. Infrared absorption and glass transition temperature were obtained via attenuated total reflectance‐dynamic mechanical thermal analysis combined testing. The glass transition temperature decreases in epoxy materials after ageing, while it increases in thermoplastic materials. The attenuated total reflectance analyses have shown a slight but irreversible change in the molecular structure of the epoxy matrix and at the fiber–matrix interface in polyphenylene sulphide composite materials. Finally, the results of the experiments give us useful suggestions for the design of vehicle structural components that are exposed to environmental conditions (rain, snow and humidity).